An interactive approach to learning economics: the WinEcon package - Jean B. Soper; Alexander B. MacDonald (Association for Learning Technology, 1994)
Under the TLTP initiative, the Economics Consortium is developing an interactive computerbased learning package called WinEcon. The package is directed at first-year economics undergraduates, particularly those taking economics as a supplementary course. Using recent technological developments, the aim is both to facilitate a further increase in student numbers without a proportionate increase in teaching staff, and to provide a better method of student learning. Some key elements of WinEcon are set out in this paper and demonstrated by screens produced at Leicester University. Methods of presenting textual information that give the user control over accessing it are described. For learning difficult concepts, a visual active learning approach is discussed. It involves user interaction and step-by-step analysis. The importance of flexibility and choice is emphasized, and the capacity of the computer to assist in deepening and consolidating learning is shown.